Burden of Transport-Related Injuries in the Eastern Mediterranean Region: A Systematic Analysis for the Global Burden of Disease Study 2017 - Saeid Safiri (3713035) (2021)
Background Transport-related injuries (TIs) are a substantial public health concern for all regions of the world. The present study quantified the burden of TIs and deaths in the Eastern Mediterranean region (EMR) in 2017 by sex and age. Methods TIs and deaths were estimated by age, sex, country, and year using Cause of Death Ensemble modelling (CODEm) and DisMod-MR 2.1. Disability-adjusted life years (DALYs), which quantify the total burden of years lost due to premature death or disability, were also estimated per 100000 population. All estimates were reported along with their corresponding 95% uncertainty intervals (UIs). Results In 2017, there were 5.5 million (UI 4.9–6.2) transport-related incident cases in the EMR – a substantial increase from 1990 (2.8 million; UI 2.5–3.1). The age-standardized incidence rate for the EMR in 2017 was 787 (UI 705.5–876.2) per 100000,which has not changed significantly since 1990 (-0.9%; UI -4.7 to 3). These rates differed remarkably between countries, such that Oman (1303.9; UI 1167.3–1441.5) and Palestine (486.5; UI 434.5-545.9) had the highest and lowest age-standardized incidence rates per 100000, respectively. In 2017, there were 185.3 thousand (UI 170.8–200.6) transport-related fatalities in the EMR – asubstantial increase since 1990 (140.4 thousand; UI 118.7–156.9). The age-standardized death rate for the EMR in 2017 was 29.5 (UI 27.1–31.9) per 100000, which was 30.5% lower than that found in 1990 (42.5; UI 36.8–47.3). In 2017, Somalia (54;UI 30–77.4) and Lebanon (7.1; UI 4.8–8.6) had the highest and lowest age-standardized death rates per 100,000, respectively. The age-standardised DALY rate for the EMR in 2017 was 1,528.8 (UI 1412.5–1651.3) per 100000, which was 34.4% lower than that found in 1990 (2,331.3; UI 1,993.1–2,589.9). In 2017, the highest DALY rate was found in Pakistan (3454121; UI 2297890-4342908) and the lowest was found in Bahrain (8616; UI 7670-9751). Conclusion The present study shows that while road traffic has become relatively safer (measured by deaths and DALYs per 100000 population), the number of transport-related fatalities in the EMR is growing and needs to be addressed urgently. Other Information Published in: Archives of Iranian Medicine License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://doi.org/10.34172/aim.2021.74